Taylor's Handbook of Clinical Nursing Skills: a nursing process approach - Lynn, Pamela (Philadelphia; Wolters Kluwer, 2008)
"Taylor's Handbook of Clinical Nursing Skills is a step-by-step guide to basic and advanced nursing skills. This book will be a quick reference tool for review of cognitive and technical knowledge and will assist students and practicing nurses to provide safe and effective healthcare. It is an ideal companion to any nursing skills or nursing fundamentals text, including Lynn, Taylor's Clinical Nursing Skills and Taylor, Fundamentals of Nursing: The Art and Science of Nursing Care"--
Abridgement of: Taylor's clinical nursing skills / Pamela Lynn. 3rd ed. c2011.
Keywords: Nursing Process; clinical nursing skills